THE FEATURES OF DESIGNING OF PSYCHODIAGNOSTIC ONLINE TESTING SYSTEMS. NEW ISSUES AND CLASSICAL APPROACHES - Zurabyan , A.M. (Modern Psychology, 2020)
Generally, the article presents the features of designing psychodiagnostic online testing systems and the main issues existing in the field. In particular, the issues have to do not only with providing validity and flexibility of similar systems but also with the security of personal information. According to the literature review, it has become clear that the online testing systems and, in particular, the tests themselves are distributed to precisely divided groups and have their spheres of application and design features. Based on the results of the analysis conducted, it can be concluded that psychodiagnostic online testing systems need not only fundamental perfection but also solutions of the issue of professional adaptation, personal identification and creation of special conditions of use for people with disabilities.
Keywords: digitalization; online systems; online researches; static structure; psychodiagnostic systems